Improvement of management information system to facilitate recording and reporting for Integrated Health Service cadres - Putu Ika Farmani; Putu Ayu Laksmini; I Kadek Arya Sugianta (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
In the Penatih Dangin Puri Village area, the Integrated Health Service (posyandu) activities data recording by cadres is still carried out manually using forms which are then recorded again in the SIP book. This data recording system still has many shortcomings, so this community service aims to provide an integrated recording system and provide training to facilitate posyandu data recording and reporting activities. Carried out in the form of training and implementation related to data entry and making reports for toddler posyandu based on the posyandu Information System (SIPOS). SIPOS training activities with Human Development Cadre partners in Penatih Dangin Puri Village began on September 27 2023. Attended by 65 cadres from 13 Banjars. Latter evaluation has been carried out and shows that the average accuracy of using SIPOS after training is 80 percent and increased to 94 percent after implementation. With the level of accuracy in filling out the data entry and report extract features, most of them have a percentage of >80 percent, but there is an accuracy level of <80 percent, namely in the date of birth entry feature (55 percent) and entering the date of visit (51 percent). Community service activities succeeded in improving cadres' skills in recording and reporting information system-based posyandu data.